2002
DOI: 10.1364/josaa.19.002449
|View full text |Cite
|
Sign up to set email alerts
|

Polaritons in hollow cylinders in the presence of a dc magnetic field

Abstract: We study the effects of a dc external magnetic field on the polaritons propagating in hollow dielectric cylinders, taking into account the retardation effects. In solving Maxwell's equations we show that only the TM modes can propagate in these systems, and we obtain the dispersion relation of the confined-surface-polariton modes. The effects of geometric parameters and the external magnetic field on the propagation of surface-polariton modes are also analyzed and show significant influence on the behavior of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The internal energy flow can be positive or negative, in contrast of that it occurs in the field absence [4], where the energy flow is always negative inside the cylinder. The signal of the energy flow determines the propagation direction, what it is confirmed by the determination of the speed of transport of the energy, by the analysis of the dispersion relation [2]. The energy flow decreases when the external magnetic field increases.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The internal energy flow can be positive or negative, in contrast of that it occurs in the field absence [4], where the energy flow is always negative inside the cylinder. The signal of the energy flow determines the propagation direction, what it is confirmed by the determination of the speed of transport of the energy, by the analysis of the dispersion relation [2]. The energy flow decreases when the external magnetic field increases.…”
Section: Discussionmentioning
confidence: 75%
“…The presence of a magnetic field applied on a semiconductor cylindrical system, causes significant alterations in the modes of propagation of polaritons. One of the main effects of the application of the field is to promote the decoupling between the electric transverse (TE) and the magnetic transverse (TM) modes, by the elimination of the TE mode [2].…”
Section: Introductionmentioning
confidence: 99%
“…The properties of polaritons has been studied since many years by many authors in different geometries [1][2][3]. However, the recent development of new techniques of producing micron-size materials, the intense current interest in lefthanded materials, and the enhanced transmission through subwavelength holes updated the interest on the study of this kind of electromagnetic excitation.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the study of polaritons in microcavities has received a great deal of attention nowadays. Surface plasmon polaritons play a particularly important role in light-matter interactions at the nanometer scale, improving their performance in biology, nanotechnology, and materials sciences [4,7]. In the study reported here, we have analyzed the propagation of surface polaritons in coaxial cylinders made of GaN and AlN.…”
mentioning
confidence: 99%
“…The energy flow shows its maximum of intensity in the internal region II, concentrated in the inner interfaces. Different from the case of massive cylinder [5][6][7], it was possible to make a correlation between the branches and the interface where the propagation of energy occurs. The energy density presents similar behavior to the energy flow.…”
mentioning
confidence: 99%